Exploring district implementation of national guidelines and maintenance of essential health services during the COVID-19 pandemic in Uganda - Fredrick E Makumbi; Freddie Ssengooba; Charles Olaro; Dorit Talia Stein; Adrian Ssessanga; Jesca Nsungwa Sabiiti; Betty Kyaddondo; Catherine Mbabazi (BMJ Public Health)
Introduction The effectiveness of national policies in decentralised health systems depends on local-level implementation. This study examines whether variation in implementation of national guidelines across districts and health system functions explains differences in local health system performance in maintaining continuity of essential maternal health, family planning and child vaccination services during the COVID-19 pandemic in Uganda.Methods We used routine health data and an interrupted time-series analysis to estimate district-specific relative declines in service outputs during COVID-19 compared with expected volumes if prepandemic trends continued for maternal health, family planning and child vaccination services. We randomly selected 57 districts across 15 regions and measured the implementation of national guidelines for maintaining essential health services through a web-based survey of district health teams. We generated ‘implementation summary scores’ by health system function and service category, representing the proportion of guidelines reported implemented by districts. We tested associations between implementation scores and performance.Results On average, districts (n=42; 74% response rate) reported implementing 58% (95% CI 54–62) of guidelines across health system functions, ranging from 33% (24–41) for ‘financing’ and 43% (36–49) for ‘service delivery’ to 93% (89–96) for ‘coordination and communication’ and 88% (81–94) for ‘monitoring’. Districts reported implementing 60% (53–68) of guidelines requiring national government action. District performance in maintaining child vaccination services was positively associated with vaccine-specific ‘financing’ and ‘national government’ implementation summary scores after controlling for geography and district characteristics.Conclusion Variation in implementing national-level policy across districts indicates inefficiencies or inequities across geographies in Uganda in terms of ability and capacity to respond to emergencies. Local guideline implementation also varied across health system functions, with financing and service delivery-related guidelines having the lowest implementation scores. Future emergency responses should consider how to balance local adaptations with central support by identifying which health system functions districts can more easily manage and adjust independently.